THE AGE-HARDENING MECHANISM OF Au585Ag90Cu264Zn61 GOLD ALLOY FOR JEWELRY PRODUCTION - Radiša Perić; Zoran Karastojković; Zorica Kovačević; Dragoslav Gusković (Journal of Engineering & Processing Management, 2013)
The researches in this paper are conducted on Au585Ag90Cu264Zn61 gold alloy for jewelry production by plasic processing. Jewelry manufacturing, in contemporary goldsmith industry, beside modern design and great appearance, also demands great mechanical and technical and technological properties. In ternary alloys of Au-Ag-Cu system, structural changes happens, but not yet inestigated enough, both in alloys and in different stages of processing. In this paper, beside theoretical explanation of hardening mechanism by annealing on temperatures below the recrystallization temperatre that is by aging, the results obtained by annealing are also presented.
Keywords: Gold alloy 585/1000; Age-Hardening; Crystal structure; Microstructure